Bimbingan Agama Islam Bagi Muallaf Di Muallaf Center Indonesia (MCI) - Umin, Ita; Aisyah, Umi; Setiawati, Rini (BINA' AL-UMMAH, 2019)
This study discusses how the implementation of Islamic guidance for converts at the Indonesian Branch of Muallaf Center (MCI) Lampung Branch. The purpose of this study is to determine the process of Islamic religious guidance for converts at the Indonesian branch of the Muslim Center (MCI) Lampung. This research is a field research with a qualitative approach and analytical nature. The technical analysis of the data used in this study is data collection, data reduction, data presentation, and drawing conclusions or verification. There are 5 stages of the implementation of Islamic guidance, namely, case identification, diagnosis, prognosis and evaluation. At the therapy stage or the implementation of assistance there are 3 steps: opening, opening and preparation. Activities, while the Islamic guidance activities carried out include the delivery of material, prayer practice, guidance on reciting and learning to read hijaiyah letters, lectures, and ongoing guidance. And the last is evaluation, evaluating and follow-up given in the next week. From the implementation of Islamic guidance that has been carried out obtained positive results on converts who previously did not understand the prayer readings and sequences in prayer, can perform prayers properly and correctly, who previously could not distinguish and read hijaiyyah letters to understand how to read them.